DEGRADASI MUTU PEMBELAJARAN MADRASAH ALIYAH NEGERI SEBAGAI DAMPAK PANDEMI COVID 19 - Mizani, Hilmi; M. Ramli, M. Ramli (Sekolah Tinggi Agama Islam (STAI) Al-Ma'rif Buntok, 2024)
Learning with direct interaction between teachers and students in the classroom has many advantages compared to indirect interaction via online media. However, with the prohibition on crowding and face-to-face meetings to avoid exposure to the Covid 19 virus, online learning has become an inevitable choice. With the limitations of online learning, it can result in degradation of the quality of learning. Therefore, this research aims to reveal the degradation of learning quality at State Madrasah Aliyah as a result of the Covid-19 pandemic in South Kalimantan. This research uses a mixed type of research, namely mixing qualitative research and quantitative research. The research design uses a Concurrent Triangulation Strategy. The subjects of this research were Islamic Religious Education teachers at State Madrasah Aliyah in South Kalimantan. A sample of 29 people were taken from all research subjects who were determined randomly. Meanwhile, the analysis technique used uses qualitative descriptive analysis and statistical analysis with the t test formula This research found that the Covid 19 pandemic has resulted in a significant degradation of the quality of learning at State Madrasah Aliyah in South Kalimantan. Degradation/decrease in the quality of learning occurs in a decrease in the quality of the learning process and a decrease in learning achievement. All indicators of the quality of the learning process show a decline. Likewise, student learning outcomes decreased.